2023
DOI: 10.3390/su15076272
|View full text |Cite
|
Sign up to set email alerts
|

Structuring and Measuring Environmental Sustainability in the Steel Sector: A Single Case Study

Abstract: Climate change policies are affecting the economic and structural viability of European Union (EU) industries, particularly in the energy-intensive sector, with very challenging goals of EU Agenda 2030 in terms of CO2 reductions and energy efficiency. This ecological transition can be supported by the employment of innovative technologies, enabling production process efficiency, resource optimization and supply-chain integration. Nevertheless, it is still empirically unclear how energy-intensive industries wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…While this was possible, the authors reveal that many HEIs had not grabbed the opportunity and were being left behind. The study design fell within the mixed methods approach that focused on UNISA as a single case study (Yazan, 2015;Dorta-González and Dorta-González, 2023;Tolettini and Di Maria, 2023). As a case study, the boundaries could easily be identified as UNISA academic staff.…”
Section: The Challenges and Prospects For Sdgs Localisation In Heismentioning
confidence: 99%
“…While this was possible, the authors reveal that many HEIs had not grabbed the opportunity and were being left behind. The study design fell within the mixed methods approach that focused on UNISA as a single case study (Yazan, 2015;Dorta-González and Dorta-González, 2023;Tolettini and Di Maria, 2023). As a case study, the boundaries could easily be identified as UNISA academic staff.…”
Section: The Challenges and Prospects For Sdgs Localisation In Heismentioning
confidence: 99%
“…Hence, the formulation of indicators solely depends upon the nature, type and size of industry. In the case of steel industries, the carbon footprint is the key performance indicator and the market perspective as one of the crucial enabler for environmental strategies [24]. Carbon footprint is the measure of greenhouse gas emission and indirectly evaluate air pollution.…”
Section: Environmental Indicatorsmentioning
confidence: 99%
“…Hence via systematic literature review, the following indicators are identified and shown in table 1 below. ENI2 Water pollution [32]; [3]; [33]; [29]; [2]; [25]; [10] ENI3 Waste Reduction and Management [32]; [3]; [33]; [2]; [33]; [29]; [34]; [35]; [25]; [30] ENI4 Air pollution [32], [3], [29], [2], [33], [34]; [27]; [10] ENI5 Material efficiency [24], [29], [33] ENI6 Ecological Impacts…”
Section: Environmental Indicatorsmentioning
confidence: 99%
“…It is confirmed that the greatest climate-altering potential comes from fertilizer production, with percentages ranging from 55% of total emissions in LAA1 to 50% in LAA3. This is followed by emissions from irrigation due to increased use resulting from increasingly dry summers in Italy in recent years, the use of nitrogen fertilizers, and crop operations [60,61]. The irrigation item, which is the main discriminating factor between the different LAAs, assumes decreasing importance going from LAA1 (20.4%) to LAA2 (16.1%) and finally to LAA3 (13.9%).…”
Section: Carbon Footprintmentioning
confidence: 99%